Five-year review of intraoperative pathology consultation in a single institution. - Wang, Liping; Leng, Bing; Rampisela, Debby (Baylor University Medical Center Proceedings, 2021)
Intraoperative pathology consultation plays an important role in the management of surgical patients and is also a measure for quality control in surgical pathology. A retrospective study was conducted to review intraoperative consultation during a 5-year period at a single institution. There were 19,145 intraoperative pathology consultation cases, including 19,026 concordant cases, 71 (<1%) frozen discordant cases, 11 (<1%) gross discordant cases, and 37 (<1%) deferred cases. Among frozen discordant cases, the most common cause for discordance was histologic sampling error (52.1%), followed by misinterpretation (42.3%). The most common major (clinically significant) frozen discordance was histologic sampling error for skin margins (32.4%), followed by histologic sampling error for lymph node metastasis (13.5%). Although our discordant rate (0.43%) was lower than that in previously reported studies (2%–8%), our major discordant rate was relatively high (50%). This review suggests that deeper sectioning of the blocks could improve the quality of our intraoperative consultations.